Phenology in a warming world: differences between native and non‐native plant species. (28th May 2019) - Zettlemoyer, Meredith A.; Schultheis, Elizabeth H.; Lau, Jennifer A.
Abstract: Phenology is a harbinger of climate change, with many species advancing flowering in response to rising temperatures. However, there is tremendous variation among species in phenological response to warming, and any phenological differences between native and non‐native species may influence invasion outcomes under global warming. We simulated global warming in the field and found that non‐native species flowered earlier and were more phenologically plastic to temperature than natives, which did not accelerate flowering in response to warming. Non‐native species' flowering also became more synchronous with other community members under warming. Earlier flowering was associated with greater geographic spread of non‐native species, implicating phenology as a potential trait associated with the successful establishment of non‐native species across large geographic regions. Such phenological differences in both timing and plasticity between native and non‐natives are hypothesised to promote invasion success and population persistence, potentially benefiting non‐native over native species under climate change.